2022
DOI: 10.1002/mawe.202100397
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between brick and stone aggregate concrete using rice husk ash as partial cement replacement

Abstract: Today's world cannot be imagined without the application of concrete. Although as a constituent of concrete stone aggregate is mostly used, there are certain areas on this earth where it is scarcely available which leads to the use of brick aggregate. Moreover, as supplementary cementitious material, use of rice husk ash is beneficial to our environment. So, the study presents the possibility of using the brick aggregate and rice husk ash to the possible extent in making concrete by comparing stone and brick a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This observation concludes that more water allows more accumulation of rice husk ash in concrete for an effective application. Similar observations also have been done in other studies related to strength and workability [24,25,46].…”
Section: Permeability Of Concretesupporting
confidence: 89%
See 2 more Smart Citations
“…This observation concludes that more water allows more accumulation of rice husk ash in concrete for an effective application. Similar observations also have been done in other studies related to strength and workability [24,25,46].…”
Section: Permeability Of Concretesupporting
confidence: 89%
“…Additionally, the use of the material in the construction field can solve the environmental issues caused by the improper dumping of this waste material [23]. Similar to stone aggregate concrete, brick aggregate concrete properties can also be improved by the use of rice husk ash [24,25]. It was also found that the use of this material in brick aggregate concrete is more effective than in stone aggregate concrete [25].…”
mentioning
confidence: 99%
See 1 more Smart Citation